Improvement Efforts Quality of Health Services (Study at Merauke Regency General Hospital) - Muhammad Ihsan (PAPSEL Research and Consulting, 2024)
The problem formulation in this research is: 1 What services does the Merauke Regency Regional Hospital provide to the community? 2. What is the quality of health services at Merauke District Hospital? The objectives of this research are: 1. To find out and describe efforts to improve health services at the Merauke Regency Regional Hospital for the community. 2. To find out the quality of services provided by Merauke District Hospital to the community. The research results show that efforts to improve the quality of health services at the Merauke District Hospital are sufficient. This can be seen in indicators of staff capacity, availability of facilities and infrastructure, and cost capabilities. Meanwhile, the distribution of health workers has not yet been implemented. The quality of health services at Merauke District Hospital is very high in terms of indicators of reliability, trust and empathy. The quality of health services at the Merauke District Hospital is very poor in terms of responsiveness and concrete indicators.